Growth Hormone Overexpression Induces Hyperphagia and Intestinal Morphophysiological Adaptations to Improve Nutrient Uptake in Zebrafish - Meirelles, Marcela G.; Nornberg, Bruna F.; da Silveira, Tony L. R.; Kütter, Mateus T.; Castro, Caroline G.; Ramirez, Juan Rafael B.; Pedrosa, Virgínia; Romano, Luis Alberto; Marins, Luis Fernando (Frontiers in Physiology, 2021)
The excess of circulating growth hormone (GH) in most transgenic animals implies mandatory growth resulting in a higher metabolic demand. Considering that intestine is the main organ responsible for the digestion, absorption and direction of dietary nutrients to other tissues, this study aims to investigate the mechanisms by which gh overexpression modulates the intestine to support higher growth. For this purpose, we designed an 8-weeks feeding trial to evaluate growth parameters, feed intake, and intestinal morphometric indices in adult gh-transgenic zebrafish (Danio rerio) model. In order to access the sensitivity of the intestine to the excess of circulating GH, the mRNA expression of intestine GH receptors (ghra and ghrb) was analyzed. In addition, expression of insulin-like growth factor 1a (igf1a) and genes encoding for di and tri-peptide transporters (pept1a and pept1b) were assessed. Gh-transgenic zebrafish had better growth performance and higher feed intake compared to non-transgenic siblings control. Chronic excess of GH up-regulates the expression of its cognate receptor (ghrb) and the main growth factor related to trophic effects in the intestine (igf1a). Moreover, transgenic zebrafish showed increased intestinal absorptive area and higher expression of crucial genes related to absorption of products from meal protein degradation. These results reinforce the ability of GH to modulate intestinal morphology as well as the mechanisms of assimilation of nutrients in order to sustain the energy demand for the continuous growth induced by the excess of circulating GH.